Comparación del cambio de color de dos resinas nanohíbridas con y sin sistema de pulido sumergidas en dos bebidas carbonatadas - Lesly Selena, Riofrio Riofrio (2021)
ABTRACT The present research aimed to compare the color change of two nano-hybrid resins with and without polishing system immersed in two carbonated beverages. For this purpose, an In Vitro type study was carried out, descriptive and comparative in cross-section. The Observation was applied as a technique and a data collection sheet was used as an instrument. The Vita Easyshade Digital Colorimeter was used to determine the color change. The population consisted of 60 samples of 5mm by 5mm, 30 samples of Filtek Z250 XT resin (3M ESPE) and 30 of Grandio resin (VOCO) resin which was divided into two groups, the resins that were polished with Sof-Lex Discs (3M ESPE) and those that were not polished. The experimental groups were immersed in (Coca-Cola, V220) carbonated drink, the control group was used distilled water for 12 days. The sampling was processed in the statistical program SPSS v.25. It was determined that there was color variation in the two resins compared to the initial color, with Filtek Z250 XT being most stable resin and carbonated drink (Coca-Cola) the substance causing more pigmentation. The significance analysis it was concluded that there were statistically significant differences between the resins with and without polishing system, where the pigmentation will be more noticeable in those that were not polished (p=0.00). As for the polishing systems's pigmentation and the carbonated drink, there were no statistically significant differences in the two resins showing a value of (p=0.063). Keywords: Nano-hybrid resins, Carbonated drinks, Pigmentation Reviewed by: Mgs. Hugo Romero ENGLISH PROFESSOR c.c. 0603156258